Analysis of Secondary Local Road Conditions Using the Surface Distress Index (SDI) Method in Medan Amplas District - Lubis, Edo Rizki Pradana; Hasibuan, Gina Cynthia Raphita; Anas, M. Ridwan (Universitas Ibn Khaldun Bogor, 2025)
Road network data and information and spatial supporting infrastructure are important to a road database management planning process. Medan Amplas District, Medan City has a road network divided into national authority roads, provincial roads and city roads, which is 143.14 km. The study area in this research is a flexible pavement-type secondary local road with a length of 33.12 km. The method used in this research is the Surface Distress Index (SDI) Method. SDI divides road conditions into 4, namely good condition, moderate condition, lightly damaged condition and heavily damaged condition. According to RCS or SKJ 2011, there are only 4 elements that are used as support for calculating the SDI value, namely % crack area, average crack width, number of holes, and average rutting depth. From the results of the analysis of the level of road damage in secondary local roads with flexible pavement type in Medan Amplas District, namely 51 road sections in good condition (98%) and 1 road section in fair condition (2%). It can be concluded that the condition of Secondary Local roads in Medan Amplas District is in good condition and only requires routine maintenance at certain points on each road section. The condition of the Secondary Local roads in Medan Amplas District using the SDI Method is in Good Rating, but the Denai River Inspection Road section has a rating of moderate damage.